P3.424 Testing Together: HIV/STI Testing and Diagnoses Among Male Couples, Chicago, 2011–2012. (13th July 2013) - Gratzer, B; Cates, K; Stephenson, R; Sullivan, P; Kane, J; Hoehnle, S
Abstract : Background: Couples-based HIV/STI interventions for MSM are rare although approximately two-thirds of HIV transmission occurs in primary sexual dyads. We adapted and evaluated a couples voluntary counselling and testing intervention used with heterosexuals in Africa for MSM in the U.S. Methods: Between September 2011 and November 2012, 177 male couples (354 individuals) provided consent and were enrolled in "Testing Together" at two Chicago clinics. Demographics and clinical data were abstracted from electronic medical records and an online survey. Results: Median age was 29 and a significant percentage (44%) was aged 25–34. 60% were non-Hispanic White, 21% Hispanic, and 8% Black/African-American. 34% had been together for less than three months, and 69% were together less than a year. Twenty-three participants (6.5%) tested HIV positive. Four individuals reported a previous positive HIV result and may have used to the service to disclose their status to their partner, yielding 19 (5.4%) newly identified infections. Five couples were concordantly positive (2.8%) and nine were discordant (5.1%). All four previously positive participants had discordantly negative partners. 64% of individuals (227) also tested for syphilis and five new syphilis infections were diagnosed (2.2%); one couple was concordantly newly infected. Only 27% of individuals (95) tested for gonorrhoea and Chlamydia at any anatomic site. Of these, 10 were diagnosed with gonorrhoea (10.5%) and 9 were diagnosed with Chlamydia (9.5%); one couple was concordantly positive for each gonorrhoea and Chlamydia. Conclusions: Diagnoses of all infections was high, suggesting that Testing Together effectively targeted high risk participants, who may not otherwise have received testing services. Receiving HIV/STI results together may substantially reduce the risk of transmission within primary sexual dyads and enhance partner service outcomes. Identifying mechanisms to increase the proportion of participants receiving STI tests warrants attention. Further research and investment in couples-based interventions is needed.